THE RELATIONSHIP BETWEEN PERCEIVED OF LEADER-MEMBER INTERACTION QUALITY AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR ON CONTRACT EMPLOYEES OF BANK RAKYAT INDONESIA (BRI) REGIONAL OFFICE SEMARANG - Sarah Florenzia Hapsari; Frieda N.R.H; Endah Mujiasih (Jurnal EMPATI, 2013)
The purpose of this research was to determine the relationship between perceived of leader-member interaction quality and organizational citizenship behavior on contract employees of BRI Regional Office Semarang. The population in this study is 50 employees and sample was 44 employees. Data collection using OCB scale consisting of 29 aitem (α = 0.943) and perceived of leader-member interaction quality scale consisting of 34 aitem (α = 0.926).Results of data analysis with simple regression analysis method produced correlation coefficient (rxy) of 0.756 with p = 0.000 (p <0,05). The results showed significant positive relationship direction between perceived of leader-member interaction quality with OCB on contracts employees of BRI Regional Office Semarang.